Changes in functional outcome over five years after stroke. Issue 6 (7th May 2019) - Rejnö, Åsa; Nasic, Salmir; Bjälkefur, Kerstin; Bertholds, Eric; Jood, Katarina
Abstract: Objectives: Data on the long‐term time course of poststroke functional outcome is limited. We investigated changes in functional outcome over 5 years after stroke in a hospital based cohort. Materials and Methods: Consecutive patients who were independent in activities of daily living (ADL) and admitted to a Stroke Unit at Skaraborg Hospital, Sweden for a first acute stroke from 2007 to 2009 ( n = 1, 421) were followed‐up after 3 months and thereafter annually over 5 years using a postal questionnaire. Clinical variables at acute stroke and 3 months post stroke were obtained from the Swedish Stroke Register. ADL dependency was defined as dependence in dressing, toileting or indoor mobility. Results: The proportions of survivors who reported ADL dependency remained stable throughout follow‐up (19%–22%). However, among survivors who were ADL independent at 3 months, about 3% deteriorated to dependency each year. Deterioration was predicted by age (HR 1.11; 95% CI 1.08–1.13), diabetes (HR 1.65; 95% CI 1.12–2.44), NIHSS score (HR 1.07; 95% CI 1.04–1.10), and self‐perceived unmet care needs one year post stroke (HR 2.01; 95% CI 1.44–2.81). Transitions from ADL dependency to independence occurred mainly during the first year post stroke. Improvement was negatively predicted by living alone before stroke (HR 0.41 95% CI 0.19–0.91), NIHSS score (HR 0.90; 95% CI 0.86–0.95) and ischemic stroke (vs. hemorrhagic stroke), HR 0.39; 95% CI 0.17–0.89. Conclusion: Transitions between ADL independence and dependency occur up to 5 years after stroke. Some of the factors predicting these transitions are potentially modifiable. Abstract : We investigated changes in functional outcome over 5 years after stroke in a hospital based cohort. Consecutive patients who were independent in activities of daily living (ADL) and admitted to a Stroke Unit at Skaraborg Hospital, Sweden for a first acute stroke from 2007 to 2009 ( n = 1, 421) were followed‐up after 3 months and thereafter annually over 5 years using a postal questionnaire. The proportions of survivors who reported ADL dependency remained stable throughout follow‐up (19%–22%) and of survivors who were ADL independent at 3 months, about 3% deteriorated to dependency each year.